(NiZBRANNYE STIHOTWORENIQ (B/ s (N~ASTX (B1s - (NnAWOI(B, (NaLI[ERs ((NtA[KENT(B: s (NiZDATELXSTWO ck kOMPARTII uZBEKISTANA(B, s, 1983)
(Nw PERWYJ TOM WO[LI IZBRANNYE STIHOTWORENIQ(B.s
rus
Keywords: (NsTIHOTWORENIQs